2012
DOI: 10.1186/1471-2466-12-24
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone inhibits TGF-β1-induced over-expression of collagen type I and heat shock protein 47 in A549 cells

Abstract: BackgroundPirfenidone is a novel anti-fibrotic and anti-inflammatory agent that inhibits the progression of fibrosis in animal models and in patients with idiopathic pulmonary fibrosis (IPF). We previously showed that pirfenidone inhibits the over-expression of collagen type I and of heat shock protein (HSP) 47, a collagen-specific molecular chaperone, in human lung fibroblasts stimulated with transforming growth factor (TGF)-β1 in vitro. The increased numbers of HSP47-positive type II pneumocytes as well as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
90
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 30 publications
6
90
2
Order By: Relevance
“…In contrast, we did not observe any effect of pirfenidone in this context. Previous studies in human lung fibroblasts and A549 cells have shown moderate reduction of collagen I expression only at concentrations higher than those used in this study (1.0 mM vs. 1.6 and 2.7 mM pirfenidone, respectively [35,36]). The effect of pirfenidone on TGF-b-induced collagen secretion in vitro has, to our knowledge, only been studied in trabecular meshwork Statistical analysis was performed using paired two-tailed t test for comparison of FKBP10 siRNA vs. scrambled siRNA control.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast, we did not observe any effect of pirfenidone in this context. Previous studies in human lung fibroblasts and A549 cells have shown moderate reduction of collagen I expression only at concentrations higher than those used in this study (1.0 mM vs. 1.6 and 2.7 mM pirfenidone, respectively [35,36]). The effect of pirfenidone on TGF-b-induced collagen secretion in vitro has, to our knowledge, only been studied in trabecular meshwork Statistical analysis was performed using paired two-tailed t test for comparison of FKBP10 siRNA vs. scrambled siRNA control.…”
Section: Discussioncontrasting
confidence: 50%
“…Oishi et al reported that proinflammatory, profibrotic, and proangiogenic cytokines, including TGF-β were eluted from PMX fibers used for the treatment of AE-IPF and suggested that adsorption of such cytokines onto PMX fibers might be one of the mechanisms of action involved. Because TGF-β has been reported to induce the expression of HSP47 (Hisatomi et al 2012;Nakayama et al 2008), adsorption of cytokines by PMX-DHP could decrease expression of HSP47 and thereby attenuate the progression of inflammation and fibrosis in the DAD lung. The precise effects of PMX-DHP on HSP47 expression should be investigated in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore assessed the effect of pirfenidone, which is an orally active synthetic molecule that has been recently approved for the treatment of IPF in some countries, but not in the United States (36), in the bleomycininduced lung fibrosis model using a "therapeutic" treatment regimen. Antiinflammatory and antifibrotic activities of pirfenidone had been previously demonstrated in vivo (37) and in vitro (38)(39)(40)(41). Effects of pirfenidone on the newly identified translational gene subset were monitored by QPCR at Day 14.…”
Section: Pirfenidone Attenuates Translational Gene Expression Signatumentioning
confidence: 99%